Development of agile-based quality management system application for pharmacy process optimization - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
The pharmacy industry faces increasingly complex challenges, including strict regulatory requirements and demands for high-quality services. This research aims to overcome these problems by developing an Agile-based quality management system application. The development method used is the Agile method, focusing on extreme programming (XP) to enable flexibility and responsiveness to changing user needs. The evaluation was conducted through a series of functionality and user acceptance tests. The evaluation results show that this application successfully meets user expectations, with a satisfaction rate of 78%. This research contributes to developing an effective solution for improving the pharmacy industry's operational efficiency and service quality. With the Agile approach, this application can be a handy tool for pharmacies.